2021
DOI: 10.4314/ajcem.v22i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Faecal carriage of extended-spectrum beta-lactamase-producing Enterobacteriaceae in healthy volunteers and hospitalized patients in Ouagadougou, Burkina Faso: prevalence, resistance profile, and associated risk factors

Abstract: Background: Extended spectrum beta-lactamase-producing Enterobacteriaceae (ESBL-PE) are a serious challenge to patients’ treatment. The aim of this study is to determine the prevalence of ESBL-PE, investigate the associated resistance, and analyze the associated risk factors for acquisition of ESBL-PE.Methodology: A cross-sectional study was conducted on healthy volunteers and inpatients. After obtaining informed consent, rectal swabs were collected from each participant for isolation of Enterobacteriaceae on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…ESBL genes that are often located on plasmids are particularly concerned by this phenomenon that favours their dissemination [ 26 ]. Several studies reported ESBL Enterobacterales in Burkina Faso from clinical samples [ 27 , 28 , 29 , 30 ] and in wastewater and salads [ 31 ]. In this study, we analysed ESBL-producing E. coli (ESBL- Ec ) and K. pneumoniae (ESBL- Kp ) from environmental samples from Ouagadougou, capital city of Burkina Faso.…”
Section: Introductionmentioning
confidence: 99%
“…ESBL genes that are often located on plasmids are particularly concerned by this phenomenon that favours their dissemination [ 26 ]. Several studies reported ESBL Enterobacterales in Burkina Faso from clinical samples [ 27 , 28 , 29 , 30 ] and in wastewater and salads [ 31 ]. In this study, we analysed ESBL-producing E. coli (ESBL- Ec ) and K. pneumoniae (ESBL- Kp ) from environmental samples from Ouagadougou, capital city of Burkina Faso.…”
Section: Introductionmentioning
confidence: 99%